Changes in Morphometric and Physiological Parameters of Oat (Avena sativa L.) Caused by Fluoride Contamination - Eugenia Krasavtseva; Dmitriy Makarov (International Journal of Plant Biology)
The article presents the results of the study of the effect of fluoride on the morphometric and physiological parameters of higher plants. The test culture was the seeds of oat Avena sativa L. Phytotesting was carried out according to standard methods in eluate and contact versions. Four different levels (0.09, 0.9, 9 and 90 mgF/L) of NaF solution for eluate phytotesting and five levels (10, 100, 500, 1000 and 2000 mgF⸱kg−1 dry soil) for contact phytotesting were applied. The decrease in root length, plant height and biomass at the maximum pollution level (90 mgF/L and 2000 mgF⸱kg−1 dry soil, respectively) relative to the control was 35.5, 23.86 and 62.47%, respectively. Statistical data processing was conducted. In addition, using a portable mini-spectrometer for leaves CI-710S, indices characterizing changes in chlorophyll content in plants were determined: Chlorophyll Content Index, Green Chlorophyll Index, Red-Edge Chlorophyll Index, Leaf Chlorophyll Index, Soil–Plant Analysis Development. The decrease in CCI, CI Green, CI Red, LCI, and SPAD indices at the maximum pollution level (2000 mgF⸱kg−1 dry soil) relative to the control was 86.2, 42.0, 57.9, 32.8 and 70.4%, respectively. Correlation analysis using the Pearson coefficient made it possible to establish a significant relationship between individual morphometric and physiological indicators. It was found that high levels of soil fluoride contamination cause significant changes in the morphometric and physiological parameters of Avena sativa L. The results of the study may have implications for agriculture or environmental protection in areas exposed to fluoride.